Gastric crystal-storing histiocytosis with concomitant mucosa-associated lymphoid tissue lymphoma - Mee Joo; Nam-Hoon Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2020)
Crystal-storing histiocytosis (CSH) is a rare entity that is characterized by intrahistiocytic accumulation of crystallized immunoglobulins. CSH is not a malignant process per se, but the majority of CSH cases are associated with underlying lymphoproliferative disorder. Although CSH can occur in a variety of organs, gastric CSH is very rare. We present a localized gastric CSH with concomitant mucosaassociated lymphoid tissue (MALT) lymphoma, manifesting as an ulcer bleeding in a 56-year-old man. Histologically, the biopsied gastric mucosa demonstrated expansion of the lamina propria by prominent collections of large eosinophilic mononuclear cells containing fibrillary crystalloid inclusions. Immunohistochemical studies revealed that the crystal-storing cells were histiocytes harboring kappa light chain-restricted immunoglobulin crystals. Within the lesion, atypical centrocyte-like cells forming lymphoepithelial lesions were seen, consistent with MALT lymphoma. Since this entity is rare and unfamiliar, difficulties in diagnosis may arise. Particularly, in this case, the lymphomatous area was obscured by florid CSH, making the diagnosis more challenging.